Probing the Structure of Quantum Mechanics 2002
DOI: 10.1142/9789812778024_0006
|View full text |Cite
|
Sign up to set email alerts
|

State Property Systems and Closure Spaces: Extracting the Classical en Nonclassical Parts

Abstract: The general approaches to quantum mechanics make use of mathematical structures that allow the description of pure quantum entities and pure classical entities, as well as mixtures of both. In this article we study the Geneva-Brussels approach, where the basic physical concepts are the one of state and 130 Probing the Structure of Quantum Mechanics Downloaded from www.worldscientific.com by KAINAN UNIVERSITY on 02/09/15. For personal use only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Applying analogous techniques to those in Aerts et al (1999, 2002), it can be proven that λ (M) is a closure space. Further structural results about SCOP can be obtained along the lines of Aerts et al (2001 2005), Aerts and Deses (2002, 2005). Having introduced this closure space the supremum can be given a topological meaning, namely for e , f ∈M we have λ ( e ∨ f )= λ ( e )∪ λ ( f ) where λ ( e )∪ λ ( f ) is the closure of λ ( e )∪λ( f ), which is obtained exactly, in the case of the linear Hilbert space introduced in Aerts and Gabora (2005), by adding the superposition states to the set λ ( e )∪λ( f ).…”
Section: The Basic Structure Of Scopmentioning
confidence: 99%
See 1 more Smart Citation
“…Applying analogous techniques to those in Aerts et al (1999, 2002), it can be proven that λ (M) is a closure space. Further structural results about SCOP can be obtained along the lines of Aerts et al (2001 2005), Aerts and Deses (2002, 2005). Having introduced this closure space the supremum can be given a topological meaning, namely for e , f ∈M we have λ ( e ∨ f )= λ ( e )∪ λ ( f ) where λ ( e )∪ λ ( f ) is the closure of λ ( e )∪λ( f ), which is obtained exactly, in the case of the linear Hilbert space introduced in Aerts and Gabora (2005), by adding the superposition states to the set λ ( e )∪λ( f ).…”
Section: The Basic Structure Of Scopmentioning
confidence: 99%
“…Most of the results obtained in quantum axiomatics can be applied readily to concepts being considered as entities with properties. Borrowing from the study of State Property Systems (Aerts, 1999a, b, Aerts et al , 1999, 2002, 2001; Aerts and Deses, 2002, 2005) we introduce the function Equation 26, Equation 27 and Equation 28 that has been called the “Cartan Map” in the study of State Property Systems. Clearly we have for a ∈L Equation 29 and for a , b ∈L Equation 30 The Cartan Map introduces a closure space, namely κ (L).…”
Section: The Basic Structure Of Scopmentioning
confidence: 99%
“…More concretely, the axiom of state determination in a state property system [1] is equivalent with the T 0 separation axiom of the corresponding closure space [44,45], and the axiom of atomicity in a state property system [1] is equivalent with the T 1 separation axiom of the corresponding closure space [46,47]. More recently it has been shown that 'classical properties' [4,6,8,9] of the state property system correspond to clopen (open and closed) sets of the closure space [48,49,50], and, explic-itly making use of the categorical equivalence, a decomposition theorem for a state property system into its nonclassical components can be proved that corresponds to the decomposition of the corresponding closure space into its connected components [48,49,50]. …”
Section: Identifying the Categorical Structurementioning
confidence: 99%
“…This is the reason the we prefer to call the type of classicality that we introduce here d-classicality. In [50] the structure related to d-classical entities is analyzed in detail.…”
Section: Definition 14 (Deterministic Statementioning
confidence: 99%
“…We also want to study this "inverse" structure for the closure space that is connected through a categorical equivalence to the state property system, an equivalence of categories that has shown to be very fruitful for many other fundamental aspects of quantum axiomatics (Aerts et al, 1999a,b, in press-a,b;Aerts and Deses, 2002;van der Voorde, , 2001van Steirteghem, 2000). We also introduce two "weakest" ortho axioms to make the lattice of properties of our ortho state property system to be equipped with an orthocomplementation, a necessary structure for quantum axiomatics (Aerts, 1981(Aerts, , 1982(Aerts, , 1983Piron, 1976Piron, , 1989Piron, , 1990.…”
Section: Introductionmentioning
confidence: 99%